2009
DOI: 10.1536/ihj.50.591
|View full text |Cite
|
Sign up to set email alerts
|

Procoagulant State in Heart Failure With Preserved Left Ventricular Ejection Fraction

Abstract: SummaryThe impact of heart failure with preserved left ventricular ejection fraction (LVEF) on activated hemostasis is still unclear. We sought to compare the activation of hemostasis in patients with heart failure with preserved LVEF, with impaired LVEF, and in healthy controls. Biomarkers of coagulation and fibrinolysis (D-dimer, tPA and PAI-1) were determined in outpatients with chronic stable (NYHA I-III), optimally managed heart failure with preserved LVEF (n = 46) and with impaired LVEF (n = 52), and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 34 publications
(31 reference statements)
0
41
0
Order By: Relevance
“…2,3 First, patients with HF may have stasis of blood flow (blood flow abnormalities) related to left ventricular systolic dysfunction and dyskinesis. 4,5 Second, patients with HF also have endocardial and endothelial dysfunction (vessel wall abnormalities). 4,5 Both of these problems may also lead to cerebral hypoperfusion and cerebral blood flow dysregulation, further increasing the risk of stroke.…”
Section: Hf Particularly Hf With Reduced Ejection Fraction (Hf-ref)mentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 First, patients with HF may have stasis of blood flow (blood flow abnormalities) related to left ventricular systolic dysfunction and dyskinesis. 4,5 Second, patients with HF also have endocardial and endothelial dysfunction (vessel wall abnormalities). 4,5 Both of these problems may also lead to cerebral hypoperfusion and cerebral blood flow dysregulation, further increasing the risk of stroke.…”
Section: Hf Particularly Hf With Reduced Ejection Fraction (Hf-ref)mentioning
confidence: 99%
“…4,5 Second, patients with HF also have endocardial and endothelial dysfunction (vessel wall abnormalities). 4,5 Both of these problems may also lead to cerebral hypoperfusion and cerebral blood flow dysregulation, further increasing the risk of stroke. Third, patients with HF have a hypercoagulable state (abnormal blood constituents).…”
Section: Hf Particularly Hf With Reduced Ejection Fraction (Hf-ref)mentioning
confidence: 99%
See 1 more Smart Citation
“…[3,8] HF has been shown to be an independent risk factor for stroke in AF and the presence of both conditions together leads to an increase in stroke severity and all-cause mortality [5,7,32,33]. Stroke in HF is most commonly associated with AF, however there is evidence that HF 'per se' even in the absence of AF also confers a hypercoagulable state [34,35]. Data from a recent meta-analysis comparing outcomes of patients with atrial fibrillation and HFrEF versus HFpEF have demonstrated that there were no significant differences in the risk of stroke between the two (RR 0.85, 95% CI 0.70-1.03, p=0.094) [26].…”
Section: Stroke Risk In Atrial Fibrillation and Heart Failurementioning
confidence: 99%
“…In patients with chronic heart failure (CHF), the activation of the sympathetic nervous system and the reninangiotensin-aldosterone system induces a hypercoagulable state, increased aggregation of thrombocytes, and reduced fibrinolysis [1,2]. Moreover, CHF patients have endothelial dysfunction, malfunction of cerebral autoregulation and rheological alterations consistent with flow abnormality via low cardiac output and aberrant flow through dilated cardiac chambers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%